2021
DOI: 10.1038/s41467-020-20593-3
|View full text |Cite
|
Sign up to set email alerts
|

SCISSOR: a framework for identifying structural changes in RNA transcripts

Abstract: High-throughput sequencing protocols such as RNA-seq have made it possible to interrogate the sequence, structure and abundance of RNA transcripts at higher resolution than previous microarray and other molecular techniques. While many computational tools have been proposed for identifying mRNA variation through differential splicing/alternative exon usage, challenges in its analysis remain. Here, we propose a framework for unbiased and robust discovery of aberrant RNA transcript structures using short read se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 49 publications
(81 reference statements)
0
10
0
Order By: Relevance
“…6D and E). Using an algorithm (SCISSOR) for calculating the risk score of each single cell [27], we also validated that monocytic leukemic cells rather than leukemic progenitors are profoundly deleterious for diseases progression, as assessed by CD34/CD11b labeling and the in silico inferring (Fig. 6F).…”
Section: Potential Association Of the Four Prioritized Genes In Venet...mentioning
confidence: 71%
“…6D and E). Using an algorithm (SCISSOR) for calculating the risk score of each single cell [27], we also validated that monocytic leukemic cells rather than leukemic progenitors are profoundly deleterious for diseases progression, as assessed by CD34/CD11b labeling and the in silico inferring (Fig. 6F).…”
Section: Potential Association Of the Four Prioritized Genes In Venet...mentioning
confidence: 71%
“…RNA-seq BAM files for TCGA LUAD samples were used as input to SCISSOR (Choi et al, 2021) for analysis of structural changes in RNA transcripts. Briefly, SCISSOR is a statistical method for unsupervised screening of a range of structural alterations in RNA-seq data including alternative splicing, intron retention, de novo splice sites, intra-/intergenic deletions, and alternative transcription start/ termination.…”
Section: Scissor Analysismentioning
confidence: 99%
“…The TCGA reference dataset includes this information together with bulk RNA-sequencing data. Using the recently published computational method SCISSOR (Choi et al, 2021) we evaluated the association of atlas-derived cell type transcriptomic signatures with genotype and survival data from the TCGA reference dataset including 1026 patients (UICC I-IV, LUAD and LUSC). In a previous pan-cancer study using bulk RNAseq data we have shown that genomic features including mutational load, tumor heterogeneity, and specific driver genes determine immune phenotypes (Charoentong et al, 2017).…”
Section: Resultsmentioning
confidence: 99%